Injection and storage of CO2 - Efficient method for increasing Oil recovery (Geo-Eco-Marina, 2019)
The paper shows the advantages of technological CO2 injection in Romanian oil deposits, the main ones being the increase of oil production and gathering the necessary data for optimal geological storage of CO2. Several Romanian oil fields where geological storage of CO2 may be applied after technological injection of CO2 are also presented
Keywords: CO2 storage; enhanced oil recovery; CO2 utilization